A late Miocene hominid partial pelvis from Hungary. Issue 136 (November 2019) - Ward, Carol V.; Hammond, Ashley S.; Plavcan, J. Michael; Begun, David R.
Abstract: Substantial differences among the pelves of anthropoids have been central to interpretations of the selection pressures that shaped extant hominoids, yet the evolution of the hominoid pelvis has been poorly understood due to the scarcity of fossil material. A recently discovered partial hipbone attributed to the 10 million-year-old fossil ape Rudapithecus hungaricus from Rudabánya, Hungary, differs from the hipbones of cercopithecids and earlier apes in functionally significant ways. Comparisons were made to extant and other fossil anthropoids using combination of non-landmark-based and linear metrics. Measurements were taken on 3D polygonal models of hipbones collected using laser scans. These metrics capture functionally relevant morphology given the incomplete preservation of the Rudapithecus specimen. This fossil displays features that reflect changes in spinal musculature and torso structure found only in extant great and lesser apes among hominoids. Rudapithecus has an expanded cranial acetabular lunate surface related to orthograde positional behaviors, a shallow acetabulum and relatively short ischium like orangutans and hylobatids. It displays evidence of moderately coronally-oriented iliac blades as in all extant apes and Ateles, and flaring iliac blade shape of siamangs and great apes, associated with some level of spinal stiffness. However, this fossil lacks the long lower ilium that characterizes chimpanzees, gorillas and orangutans, associated with their reduction of the number of lumbar vertebrae. The R. hungaricus pelvis demonstrates that the extreme elongation of the lower ilium seen in extant great apes does not necessarily accompany adaptation to orthograde posture and forelimb-dominated arboreal locomotion in hominoid evolution. Lower iliac elongation appears to have occurred independently in each lineage of extant great apes, supporting the hypothesis that the last common ancestor of Pan and Homo may have been unlike extant great apes in pelvic length and lower back morphology.